What keeps athletes in the gym? Goals, psychological needs, and motivation of CrossFit™ participants. - Sibley, Benjamin A.; Bergman, Shawn M. (International Journal of Sport & Exercise Psychology, 2018)
The CrossFit™ workout methodology has experienced tremendous growth and popularity over the last 10 years. This programme utilises high-intensity workouts that incorporate a wide variety of calisthenics and weight lifting movements, and is typically delivered in a group format by a qualified instructor. Gaining an understanding of the motivational factors underlying CrossFit participation will benefit fitness trainers of all types. The purpose of this study was to examine the relationships among goal contents, psychological need satisfaction, behavioural regulation, and participation frequency in a sample of CrossFit athletes. Participants (n = 322) completed instruments assessing exercise goal contents, basic psychological need satisfaction, and behavioural regulations in exercise, and a survey of demographic and participation variables. Having intrinsic goals, such as developing skills or improving health, was found to predict greater psychological need satisfaction. Competence and autonomy need satisfaction were found to predict higher levels of intrinsic and identified regulations. Participation frequency was positively predicted by intrinsic regulation, intrinsic goal contents, competence need satisfaction, and was negatively predicted by external regulation. When examining the full path-analysis model, competence and autonomy basic psychological need satisfaction were found to partially mediate the relationship between goal content and intrinsic regulation. Based on these findings, health and fitness leaders can maximise participant’s intrinsic motivation by emphasising goals focused on skill learning and health. Additionally, fitness leaders should make efforts to enhance participants’ feeling of competence and autonomy.